Systematic Error in Gas Chromatography-Mass Spectrometry-Based Quantification of Hydrolyzed Urinary Steroids - Moon, Ju-Yeon; Ha, Young Wan; Moon, Myeong Hee; Chung, Bong Chul; Choi, Man Ho (AMER ASSOC CANCER RESEARCH, 2010)
Gas chromatography-mass spectrometry-based metabolite profiling can lead to an understanding of various disease mechanisms as well as to identifying new diagnostic biomarkers by comparing the metabolites related in quantification. However, the unexpected transformation of urinary steroids during enzymatic hydrolysis with Helix pomatia could result in an underestimation or overestimation of their concentrations. A comparison of beta-glucurondase extracted from Escherichia coli revealed 18 conversions of 84 steroids tested as an unexpected transformation under hydrolysis with beta-glucuronidase/arylsulfatase extracted from Helix pomatia. In addition to the conversion of 3 beta-hydroxy-5-ene steroids into 3-oxo-4-ene steroids, which has been reported, the transformation of 3 beta-hydroxy-5 alpha- reduced and 3 beta-hydroxy-5 beta-reduced steroids to 3-oxo-5 alpha-reduced and 3-oxo-5 beta-reduced steroids, respectively, was newly observed. The formation of by-products was in proportion to the concentration of substrates becoming saturated against the enzyme. The substances belonging to these three steroid groups were undetectable at low concentrations, whereas the corresponding by-products were overestimated. These results indicate that the systematic error in the quantification of urinary steroids hydrolyzed with Helix pomatia can lead to a misreading of the clinical implications. All these hydrolysis procedures are suitable for study purposes, and the information can help prevent false evaluations of urinary steroids in clinical studies. Cancer Epidemiol Biomarkers Prev; 19(2); 388-97. (c) 2010 AACR.
Keywords: BETA-GLUCURONIDASE PREPARATIONS; HELIX-POMATIA JUICE; BREAST-CANCER; ENZYMATIC-HYDROLYSIS; ESCHERICHIA-COLI; TESTOSTERONE; METABOLITES; CONVERSION; PROSTATE; DISEASE